Advances in Novel Nanomaterial-Based Optical Fiber Biosensors—A Review - Muyang Li; Ragini Singh; Yiran Wang; Carlos Marques; Bingyuan Zhang; Santosh Kumar (Biosensors, 2022)
This article presents a concise summary of current advancements in novel nanomaterial-based optical fiber biosensors. The beneficial optical and biological properties of nanomaterials, such as nanoparticle size-dependent signal amplification, plasmon resonance, and charge-transfer capabilities, are widely used in biosensing applications. Due to the biocompatibility and bioreceptor combination, the nanomaterials enhance the sensitivity, limit of detection, specificity, and response time of sensing probes, as well as the signal-to-noise ratio of fiber optic biosensing platforms. This has established a practical method for improving the performance of fiber optic biosensors. With the aforementioned outstanding nanomaterial properties, the development of fiber optic biosensors has been efficiently promoted. This paper reviews the application of numerous novel nanomaterials in the field of optical fiber biosensing and provides a brief explanation of the fiber sensing mechanism.